Gingivitis and oral health-related quality of life: a literature review - Taís de Souza Barbosa; Maria Beatriz Duarte Gavião; Fábio Luiz Mialhe (Brazilian Dental Science)
Objective: The aim of this study was to review the literature about the relationship between gingivitis and oral health-related quality of life (OHRQoL). Material and methods: Relevant databases were searched for articles in English, which had been published from October 1990 to February 2014. Two independent examiners selected relevant papers, by initially assessing the abstracts and subsequently the full-text articles. Selected studies were grouped based on clinical and OHRQoL instruments and submitted to qualitative analyses. Results: Out of 184 references, twelve were eligible for synthesis. All studies were cross-sectional and reported data from the following five different countries: Chile (n=2), India (n=1), Brazil (n=3), Thailand (n=5) and Sudan (n=1). The number and age of subjects included ranged from 53 to 9133 and from eight to 106 years, respectively. The following six OHRQoL instruments were used: Oral Health Impact Profile (OHIP), OHIP-14, Child Perceptions Questionnaire (CPQ), Oral Impacts on Daily Performance (OIDP), Child-OIDP and Geriatric Oral Health Assessment Index (GOHAI). The different methods to evaluate the presence of gingivitis were: necrotizing ulcerative gingival lesions (n=2), Gingival Index (n=2), Community Periodontal Index (n=7) and gingival bleeding after tooth brushing (n=1). Conclusion: This literature review suggests that gingivitis is associated with impairment of OHRQoL.